Fron the 7/7 London Bombings to the Failed Turkish Coup: How News Organisations Have Adapted to the Realities of Eyewitness Media - Wardle, Claire (My University, 2016)
In April 2007, 32 people were killed when a gunman opened fire on the Virginia Tech campus. Students took to the Live Journal blogs and their newly acquired Facebook accounts to talk about their experiences. The most savvy journalists found the updates and reached out to eyewitnesses causing a backlash against this type of public social newsgathering. In July 2016, the failed Turkish coup was caught on Periscope and Facebook Live by hundreds of people picking up their smartphones and broadcasting live. This lecture will examine the last decade of social newsgathering, highlighting what has changed and what hasn't. There will be a discussion of the logistics of social discovery and verification as well as the ethical considerations of protecting eyewitnesses when publishing this type of content, and ensuring journalists and audiences are not impacted by the increasingly graphic content that is emerging from breaking news events.
Keywords: Periodismo; Redes sociales; Social Media